THE AIDS EPIDEMIC IN SOUTH FLORIDA: BLACK NON-HISPANICS IN OUR COMMUNITIES REMAIN INCREASINGLY VULNERABLE - Velis, Evelio; Shaw, Graham; Blandon, Kenneth (European Scientific Journal, ESJ, 2015)
Objective. Demographic variables of individuals with AIDS were compared during two time periods (1993 - 1995 and 2011 - 2013). Incidence and mortality related data was also explored. Methods. This is an observational study. Tests of significance were performed to identify differences or associations between selected groups. A correlation analysis was conducted to identify relationships between AIDS diagnosis and socioeconomic indicators. Results. A reduction in new AIDS cases reported and AIDS-related mortality were observed. Nonetheless, AIDS is still disproportionately affecting the Black Non-Hispanic population. Black Non-Hispanic women remain particularly vulnerable to the disease. A positive correlation between AIDS diagnosis and poverty rate and the lack of health insurance and a negative correlation between AIDS diagnosis and education level was identified. Conclusion. Though the actual number of AIDS cases is declining, it continues to disproportionately discriminate against our poorer, less well educated communities. Despite the availability of improved medications, people in these communities remain particularly vulnerable.